Multilayered Cu–Ti deposition on silicon substrates for chemiresistor applications. (1st November 2020) - Torrisi, A.; Horák, P.; Vacík, J.; Cannavò, A.; Ceccio, G.; Vaniš, J.; Yatskiv, R.; Grym, J.
Abstract: On the perspective to develop CuO–TiO2 MOS, multilayered Cu and Ti thin layers were alternatively deposited on silicon wafers using 25 keV Ar + ion beam sputtering and, subsequently, oxidized by thermal annealing in air at 400 °C for 24 h. The deposited films have variable ratios of the Cu and Ti % at. One of the main goal is to obtain such multilayers avoiding the presence of Cu–Ti–O compounds. The samples were characterized in terms of composition (by RBS and SIMS analyses) and morphology (by AFM and SEM investigations). In particular, SIMS maps allows to observe the spatial distribution and thickness of each phase of the Cu/Ti multilayers, and further to observe Cu diffusion and mixing with Ti, as well as phase separation of CuO and TiO2 in the samples. The reasons of this effect represent an open issue that has to investigated, in order to improve the MOS fabrication. GRAPHICAL ABSTRACT: